2017
DOI: 10.1063/1.4975602
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of relationship between interfacial electroadhesive force and applied voltage for different substrate materials

Abstract: An experimental investigation into the relationship between the interfacial electroadhesive force and applied voltage up to 20 kV has been presented. Normal electroadhesive forces have been obtained between a double-electrode electroadhesive pad and three optically flat and different substrate materials: glass, acrylic, and polycarbonate. The results have shown that not all substrate materials are good for the generation of electroadhesive forces. Only 15.7 Pa has been obtained between the pad and the polycarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 13 publications
2
24
0
2
Order By: Relevance
“…19 In addition, there was a relative difference of 75.3% for a polyimide comb electroadhesive pad when energized at 4.4 kV and exposed to the four surface scratch directions. 11 Note that the relative difference was defined here as: (maximum value À minimum value)/minimum value  100%.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…19 In addition, there was a relative difference of 75.3% for a polyimide comb electroadhesive pad when energized at 4.4 kV and exposed to the four surface scratch directions. 11 Note that the relative difference was defined here as: (maximum value À minimum value)/minimum value  100%.…”
mentioning
confidence: 99%
“…Previous results demonstrated that: (1) the rougher the substrate surface, the smaller the electroadhesive force would be, to some extent 11 (this is because the decreasing contact areas and the increasing air inclusion and distance between the electroadhesive and the substrate cause a force reduction); (2) unstable adhesive forces would be obtained using both double-electrode and comb pad designs under different substrate surface conditions and the same substrate with differing surface scratch directions. 11,19 It is assumed that spiral and concentric electroadhesive pad designs can be independent of different interfacial surface interactions, thus producing stable adhesive forces on the same plate with different interfacial surface conditions. In order to verify this, a circular aluminium (Al) plate (thickness of 1 mm and diameter of 275 mm) was sanded by a 60 grit aluminium oxide sanding disc to produce a unidirectional surface scratch.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Electroadhesion is an electrically controllable and dynamic 8 electrostatic attraction between an electroadhesive pad and a substrate, with 33 variables influencing the interfacial electroadhesive force. 9 These variables include voltage 10,11 and material properties such as relative permittivity, [10][11][12] pad geometry, 13,14 surface texture, 15 and environmental conditions. 9,16 A typical electroadhesion system contains four main parts, including an electroadhesive pad, a power supply, a control system, and a substrate, as can be seen in Fig.…”
mentioning
confidence: 99%
“…9,10 The force tests were conducted over three days, and each test was repeated five times. A 15-time test was conducted previously to check the repeatability of the testing procedure and concluded that five times were enough to produce robust and repeatable results.…”
mentioning
confidence: 99%